Kompensasi dan Beban Kerja terhadap Turnover Intention dan Dampaknya terhadap Kinerja Karyawan bagian Produksi pada CV. Bintang Tex Indonesia - Muhammad Nafhan Syaifudin; Kustini Kustini (IPM2KPE, 2024)
This research aims to determine the effect of compensation and workload on turnover intention and its impact on employee performance on employee performance at CV. Bintang Tex Indonesia Sidoarjo. The method used in this research is a quantitative method with a saturated sampling technique. The research sample consisted of 48 CV contract employees. Bintang Tex Indonesia Sidoarjo. This research took data through a questionnaire that was distributed to CV employees. Bintang Tex Indonesia Sidoarjo. The analytical tool used in this research is Partial Least Square (PLS). The results of this study show that compensation has a negative and significant effect on turnover intention, workload has a positive and significant effect on turnover intention, turnover intention has a positive and significant effect on employee performance, workload has a negative and significant effect on employee performance, and compensation has a positive and significant effect on employee performance. Keywords: Workload, Performance, Compensation, Turnover Intention